Regional Government Authority Over Collection and Auditing Regional Taxes: Indonesia Legal Perspective - Sumerta Yasa, Putu Gede Arya; Dalem Dahana, Cokorda (Kertha Patrika, 2021)
Taxes as a source of State revenue are very important objects because most of the types of State revenue come from taxes. Due to this condition, it is necessary to have firm regulation for both tax authorities and taxpayers to maximize revenue from the tax sector. This writing aims to analyze the legality aspects of local government authorities in collecting and auditing local taxes. This is a normative legal research with a statutory approach and a conceptual approach. The results show that local government has the authority to collect local taxes as a consequence of the concept of regional autonomy, which emphasized that regional revenue is a source of financing for regional development. The Law of Local Taxation and Retribution provides greater authority to regions than before in administering regional taxes and levies. The enactment of the Regional Government Law and the Central and Regional Financial Balancing Law then regulates the expansion of tax objects and the determination of tax rates. Meanwhile, audit action in regional taxation is one of the efforts to save financial management by testing the correctness of the sustainability of financial planning and operations that are recorded in the form of taxpayer financial statements. This audit effort is part of the tax collection process regulated in the General Provisions and Tax Procedures in an effort to enforce central and regional tax collection.